Web-based human resource information management system - Baltazar, Melanie C.; Belina, Nelyn A.; Carpio, Avegail D.; Cayanan, Abigail Coleen S.; Chua, Patrick Czar A. (2001)
Web-based Human Resource Information Management System (WHIMS), with the features of some current HR software and other additional functionalities such as payroll computation, reports generation, job posting and job application inquiry, comprises a powerful tool for the management of employee's information. This system is generalized in a way that different instituions can utilize it for their Human Resource Information Management Systems. The project was able to lessen the burden of Human Resource Management by handling the entire scheme of record keeping system, which is implemented in an enhanced and improved manner. Interviews and comparative studies on different organizations and establishments were performed by the group, resulting to a comprehensive examination of the different systems of implementation of Human Resource Management Systems. Since Human Resource Management is a broad field of information technology, it is vital that several HR systems be reviewed and analyzed. Synthesis of the various aspects of such systems is crucial in discerning the basic structure of an ideal computerized HR system, which in turn facilitated in the formation of part of the structure of WHIMS. Utilization of Active Server Pages 3.0 (ASP), Hyper Text Mark-up Language (HTML), and Visual Basic Script (VBScript), were employed for the code generation of the project. Software such as Dreamweaver Ultradev and Microsoft Visual Interdev, on the other hand, were used for better interface generation.